Penelitian kualitas gas buang pada industri ban - Winahyu, Kusumo Retno; Sukaeni, Irene Sri; Dahono, Justinus Edy (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1997)
The research of air pollution quality of rubber tyre industry to check rubber tyreair pollution quality. Taking samples should be done on several tyre rubber industries in the middle of java. Each of industries observed by two samplinglocation, it was taken from rubber tyre processing area. Many result of the research shown sampling data of oxidants at processing area are 0,2580 â 1,4670 ppm higher than 0,10 ppm standar concerned, while data of oxidants at ambient quality have range 0,4144 â 1,6235 ppm higher than 0,10 ppm environmental standar quality for ambient itâs given range between 11,7034 â 18,1179 pmm NH, higher than 2,00 ppm standar quality for processing rea and the result of particles analizing area 0,2727 â 1,6880 mgr/m3 higher than 0,26 mgr.m3 standar quality for ambient. Many result of parameters still agree with standar concerned. H3S for ambient have given range between 0,0051-0,0216 ppn lower than 0,03 ppm lower than 10,00 ppm standar for processing area. The result of particles analizing for processing area have given range 1,1440 â 1,2632 mgr/m3 lovewr 10,00 mgr/m3 Â Â INTISARIÂ Penelitian kualitas gas buang pada industri Ban bertujuan untuk mnecapai dua kualitas industry gas buang industry Ban. Pengambilan contoh uji udara dilakukan pada bebrapa industry Ban di wilayah Jawa Tengah, masing0 masing diamati pada dua lokasi pengambilan sampel udara , yaitu pada ruang proses produksi serta udara ambien atau udara lingkungan disekitar pabrik. Parameter yang diteliti meliputi oksida, sulfar oksida, serta Amoniak pada lokasi sampling udara ligkungan ( ambien ) udara ruang proses bagi parameter SOx % NOx pada lokasi sampling ruang proses produksi bagi parameter NH, telah melampaui batas yang disyaratkan yaitu mempunyai kisaran sebesar 11,7034 â 18,1179 ppm < 2,00 ppm. Parameter oksidan terdeteksi sudah diatas baku mutu pada lokasi pengambilan sampel pada ruang ambien dan ruanf proses. Yaitu sebesar 0,4144 â 1,6235 ppm > 0,01 ppm untuk ruang ambien sedangkan hasil penelitian pada ruang proses yaitu sebesar 0,2580 â 1,2632 mgr/m3 < 10,00 mgr/m3.